Simuliidae (insecta: diptera) de colombia i - nueva especie de simulium (hemicnetha) (1979)
A description of all stages of development of a new species of the subgenus Hemicnetha comparing it with Simulium Mexicanum and S. lahillei, species which belong to the same sub-genus, adding some ecological notations of this new species.